750 The effect of body checking policy change on contact mechanisms in 11–12 year old ice hockey players. (1st September 2016) - Martinez, German; Janzen, Leticia; Krolikowski, Maciek; Romanow, Nicole; Palacios-Derflingher, Luz; Goulet, Claude; Nadeau, Luc; Emery, Carolyn
Abstract : Background: Hockey Canada's evidence-based body checking (BC) policy change (2013) was informed by evidence that policy allowing BC in Pee Wee (11–12 year old) ice hockey players resulted in a >3-fold increased risk of injury and concussion compared with leagues where BC was not allowed. Objective: To compare the frequency of type and intensity of physical contacts (PC) and head contact in elite (upper 30%) Pee Wee ice hockey games in leagues not allowing BC (2013–2014) compared with leagues allowing BC (2007–2008) using video analysis. Methods: Ten elite games pre-policy change (2007–2008) and 11 elite games post-policy change (2013–2014) were video recorded and analysed using a validated methodology to compare the frequency of type (trunk and other types of PC with limb/head/stick) and intensity (trunk contacts – level 1–5 intensity) of PC and head contact. Incidence rate ratios (IRR) were estimated using Poisson regression controlling for clustering by game) to compare PC before and after the BC policy change. Results: A total of 4409 trunk PCs and 2623 other PCs were observed. The total number of trunk PCs (IRR = 0.97, 95% CI: 0.83–1.14) and other contacts (IRR = 0.87, 95% CI: 0.59–1.29) did not change post-policy change. High intensity contacts (levels 4 and 5) were less frequent post-policy change (IRR4 = 0.13, 95% CI: 0.09–0.19 and IRR5 = 0.13, 95% CI: 0.07–0.26) and low intensity contacts (level 2) increased (IRR2 = 1.47, 95% CI: 1.21–1.79). Limb PCs decreased in 2013–14 (IRR = 0.48, 95% CI; 0.33–0.71) and there was no difference for head contacts (IRR = 0.81, 95% CI; 0.51–1.30). Conclusions: There were no significant differences in total number of PC by study year. However, the incidence of high intensity (level 4–5) PCs decreased post -policy change. There was no significant difference in direct head contact or total number of other contacts. This will inform the development and evaluation of injury prevention and skill training strategies in youth ice hockey.